Antyczna hybryda, diabeł w średniowieczu. Kilka uwag o źródłach wizerunków bestii w sztuce .......... 69 - First, Grzegorz (Fantastyczne stwory i bestie w dziejach i kulturze od antyku po czasy najnowsze, 2025)
AN ANCIENT HYBRID, A DEVIL IN THE MIDDLE AGES. SOME COMMENTS ON THE SOURCES OF THE IMAGES OF BEASTS IN ART One of the most important aspects of the presence of beasts and, more broadly, fantastic creatures in history and culture is their visualization – the image of the beast present in art throughout epochs. This topic is broad and multi-threaded, but it is worth focusing, among other things, on the origins of the popular and frequent image of the beast as a hybrid character, composed of a mixture of animal, human, fantastic elements and additional attributes. In the genesis of this type of representations popular especially in Medieval art, apart from written sources, also important are those of an iconographic nature from ancient cultures. In addition to Greek art, it is worth paying attention to sources from the ancient Near East and late antiquity, where the motif of fantastic beasts, often representing magical beings, could have influenced the visual representations of beasts in later times.